Valeological support of library-information activities in school libraries - V. Y. Sokolov (Библиосфера, 2017)
The article outlines general characteristics of the originality of forming valeological functions in a school library. The paper objective is to study peculiarities of the valeological support of library-information activities in school libraries, as well as the specifics analysis of their library and cultural-educational work aimed at developing the health culture of this activity subjects The author consistently reveals the peculiarities of forming the valeological function of school libraries under conditions of the information society development and dissemination of information-telecommunication technologies in libraries. The article describes cultural-educational activities of libraries directed to develop the health culture not only in readers (schoolchildren, their parents, teachers), but in librarians themselves. The author applies both general scientific methods of research (analysis, synthesis, deduction, induction, generalization, abstraction, comparative, structural-functional methods, method of system analysis, etc.) and special ones (method of analysis of analog objects, information processing, grouping). While researching the author concludes about necessity of the the following: to equip educational libraries technically; to update and strengthen the information base and book stocks of school libraries; to ensure the access of libraries to information resources, in particular the Internet; to form a unified electronic database of school library collections; to develop a form of resource integration with other educational libraries; to create a standing order on the status of libraries in basic schools; to develop a system for improving the skills of school library staff; to organize special training for school librarians to master their knowledge and skills of a healthy lifestyle. Therefore, the school librarian must be trained according to a separate professional specialization. The social life development requires librarians to know not only the valeology bases, but the ability to navigate in information technologies, school curricula and training courses diversitys. Modern problems of information education and forming a high level of valeological culture can be solved only by combining the efforts of general education institutions and school libraries, teachers and librarians. Pedagogical experience shows that knowledge on the health formation and preservation is a necessary and insufficient factor in students' personality development. To influence the behavior, informative methods should be combined with life skills of effective work and rest, physical activity, rational nutrition, an ability to analyze health issues and make appropriate decisions. Thus, forming health culture through library-information activities provides arming school readers and librarians with knowledge on social and individual health and applying certain information technologies in their activities.